2019
DOI: 10.1080/03008207.2019.1641495
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age on the severity of joint damage and intra-articular inflammation following a simulated medial meniscus injury in 3, 6, and 9 month old male rats

Abstract: Purpose: Aging is a known risk factor for osteoarthritis (OA). Several transgenic rodent models have been used to investigate the effects of accelerated or delayed aging in articular joints. However, age-effects on the progression of post-traumatic OA are less frequently evaluated. The objective of this study is to evaluate how animal age affects the severity of intra-articular inflammation and joint damage in the rat medial collateral ligament plus medial meniscus transection (MCLT+MMT) model of knee OA.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 35 publications
0
10
2
Order By: Relevance
“…Magnetic capture was used to assess intra-articular levels of IL6, CCL2, and CTXII (27). In magnetic capture, particles containing superparamagnetic iron oxide nanoparticles are used to magnetically precipitate target molecules from synovial fluid (28).…”
Section: Magnetic Capturementioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic capture was used to assess intra-articular levels of IL6, CCL2, and CTXII (27). In magnetic capture, particles containing superparamagnetic iron oxide nanoparticles are used to magnetically precipitate target molecules from synovial fluid (28).…”
Section: Magnetic Capturementioning
confidence: 99%
“…Following ELISA and particle quantification, biomarker levels were estimated as described in (28) with assay validation provided in (27,28). IL6, CCL2, and CTXII levels in rat knees were compared with one-way ANOVAs with post hoc Tukey's HSD tests when indicated.…”
Section: Magnetic Capturementioning
confidence: 99%
“…Following euthanasia via exsanguination, magnetic capture was performed in both the operated and contralateral knee, as described in (34). Briefly, 300 µg of antibody-conjugated magnetic particles (equal parts for each particle type) were suspended in 10 µL of saline, then injected in the operated and contralateral knee.…”
Section: Mechanical Overloading Osteoarthritis Gene Expression Analysis: Gene Expression Was Evaluated Bymentioning
confidence: 99%
“…Absorbance was read at 450 and 650 nm. Particles were quantified in 60 μl of capture buffer with particle suspensions read for absorbance at 450 nm using Synergy 2 Multi-Mode Microplate Reader, as described in (34).…”
Section: Mechanical Overloading Osteoarthritis Gene Expression Analysis: Gene Expression Was Evaluated Bymentioning
confidence: 99%
“…Allen et al provide important data on this issue using the combined transection of the medial collateral ligament and medial meniscus in rats at various ages. 9 The authors found more severe cartilage damage and hypertrophy in older rats, but that inflammatory factors in the synovial fluid were generally unaffected by the age at time of injury. Given the widespread attention to the "inflammaging" hypothesis, these are important data in highlighting that other age-related changes are also likely to be important in altering disease pathogenesis.…”
mentioning
confidence: 96%